The Phoenix Pencil Company : a novel - King, Allison (William Morrow, an imprint of HarperCollins Publishers, 2025)
"Monica Tsai spends most days on her computer, journaling the details of her ordinary life and coding for a program that seeks to connect strangers online. A self-proclaimed recluse, she's always struggled to make friends and, as a college freshman, finds herself escaping into a digital world, counting the days until she can return home to her beloved grandparents. They are now in their nineties, and Monica worries about them constantly--especially her grandmother, Yun, who survived two wars in China before coming to the States, and whose memory has begun to fade. Though Yun rarely speaks of her past, Monica is determined to find the long-lost cousin she was separated from years ago. One day, the very program Monica is helping to build connects her to a young woman, whose gift of a single pencil holds a surprising clue. Monica's discovery of a hidden family history is exquisitely braided with Yun's own memories as she writes of her years in Shanghai, working at the Phoenix Pencil Company. As WWII rages outside their door, Yun and her cousin, Meng, learn of a special power the women in their family possess: the ability to Reforge a pencil's words. But when the government uncovers their secret, they are forced into a life of espionage, betraying other people's stories to survive. Combining the cross-generational family saga and epistolary form of A Tale for the Time Being with the uplifting, emotional magic of The Midnight Library, Allison King's stunning debut novel asks: who owns and inherits our stories? The answers and secrets that surface on the page may have the unerasable power to reconnect a family and restore a legacy."--